Breaking bad news sensitively: what is important to patients in their last year of life?. Issue 1 (25th November 2011) - Hanratty, Barbara; Lowson, Elizabeth; Holmes, Louise; Grande, Gunn; Jacoby, Ann; Payne, Sheila; Seymour, Jane; Whitehead, Margaret
Abstract : Aim: To understand patients' perspectives on how a diagnosis of a life-limiting illness was first communicated to them. Study design: In-depth qualitative interviews with 50 people ranging in age from 30 to 93 years, diagnosed with cancer (31), heart failure (13), stroke (three) or neurological conditions (three) and thought by the responsible health professional to be in the last year of life. Participants from two areas of Northern England were recruited through specialist nurses or hospital consultants and interviewed in their current place of residence. Transcribed data were analysed using Framework. Results: Patients were most likely to recall the pace and clarity with which bad news was conveyed. A direct approach was most common, without much prior warning for the patients. Direct information was usually received well when the patient knew the health professional and when it had been suggested that the patient should be accompanied to the appointment. Some professionals did work to set the scene for the eventual news, with a gradual build-up of information, and narrowing down of options. This approach was perceived as appropriate and sensitive. People with heart failure had engaged in much less discussion about their condition, and most did not recall a specific conversation with their doctor about their prognosis. Conclusions: Bad news is not always broken in a sensitive way, despite considerable efforts to address this issue. Relatively minor changes to practice could improve the patient experience: greater preparation, provision of sufficient time in consultations and cautious disclosure for new patients.